Devianza sessuale e imperativi genealogici - Finucci, Valeria (Acta Histriae, 2007)
The paper examines the case of Margherita Farnese, whose marriage to Duke Vincenzo Gonzaga in 1581 had to be annulled because of a problematic sexual anatomy. As the the body of a rich, young and appropriately chaste princess suddenly started to be perceived as deviant so doctors from various courts converged to Mantua and Parma to give their opinion on what makes a female body typical. In working through the problematics of normal/subversive, I will discuss the medical discovery (actually, recovery) in the Renaissance of specific information about constitutive parts of the female sexual apparatus, the Church's take on what makes a marriage valid; the politicians' need to guarantee an ordered successionč and the cultural hysteria coming from an inconvenient 'hyster'
Keywords: deviškost; kulturna zgodovina; malformacija; marriage; renesansa; sexual intercourse; spodobnost; spolnost; zakonska zveza